(untitled) (Scientific journal of the Fergana State University, 2025)
This article presents an idea about the intersection of the media, national language and national culture and the emergence of a new linguistic phenomenon at this point, namely, precedent units. The study of precedent units in Uzbek and world linguistics, their realization in speech in the form of a precedent name, a precedent sentence and a precedent text, as well as their specific features are discussed. Any scientific theories presented are substantiated by practical examples.